(untitled) (Biological Sciences - PJSIR, 2011)
This study was sought to determine the fungi present in the produced water (PW) and water- soluble fraction (WSF) of crude oil as a preliminary approach to determining that fungi can survive in crude oil polluted water and their possible use in bioremediation. Different concentrations of PW and WSF of crude oil samples from Ughelli East Flow Station in Delta State of Nigeria were exposed to onion (Allium cepa) primordial cells at different concentrations for twelve days. Thereafter, samples of the PW and WSF were cultured on Potato Dextrose Agar. Isolates of Thamnidium sp, Gelasinospora sp, Zygorhynchus sp and Colletotrichum sp were found. Zygorhynchus and Colletotrichum were associated with PW while Thaminidium and Gelasinospora associated with the WSF. There were changes in the pH and turbidity of the PW and WSF before and after exposure to Allium cepa cells. At 25% level of treatments there were significant differences in pH and turbidity values of the PW and WSF at P < 0.05 and P > 0.01 before and after exposure to the plant.